Emotional intelligence and Seymour Epstein’s Cognitive-Experiential Self-Theory of Personality - Pracka, Joanna (Studia Psychologica: Theoria et praxis, 2012)
The present article is an attempt of placing a construct of Emotional Intelligence in the structure of a personality of a man. The Cognitive-Experiential Self-Theory of Epstein, that arranges different spheres of functioning of a man, refering them to different systems of processing information, was used as a point of reference. Emotional intelligence, understood as a set of abilities needed to process pieces of emotional information, as a multidimensional construct of different abilities fits in the action of experiential and rational systems - both marked out by Epstein. Each ability as a part of emotional intelligence belongseither to the firstor to the second system. One can come to a conclusion that like the majority of psychological processes of a man can be attributed to their level of unconsciousness, preconscious or conscious, so the emotional functioning on different levels of consciousness. The most basic, primary abilities of emotional intelligence belong to the experimental system of a direct regulation, whereas those developed later, evolving on the base of the first abilities, are used on the level of the rational system of the indirect regulation.